Ulcerative Colitis Preceding Asymptomatic Wilson’s Disease: A Case Report and Literature Review - Jun Kunizaki; Yuko Yoto; Yoshinobu Nagaoka; Akira Ishii; Tomoe Kazama; Kohei Wagatsuma; Noriyuki Akutsu; Aki Ishikawa; Toju Tanaka; Shintaro Sugita; Takeshi Tsugawa; Hiroshi Nakase (Gastro Hep Advances)
An 11-year-old girl with quiescent ulcerative colitis had sustained elevation of liver enzymes. Although she had no clinical symptoms suggestive of Wilson’s disease, such as Kayser–Fleischer rings, laboratory data showed decreased serum copper and ceruloplasmin levels and increased urinary copper excretion. Genetic testing showed pathogenic variants in ATP7B allele 1: c.2004_2006delGAT (p. Met668del) and allele 2: c.1708-5T>G. After starting copper chelators, her liver function normalized, and she maintained clinical and endoscopic remission of ulcerative colitis. Mutations or defective functions of ATP7B lead to hepatic dysfunction and intestinal inflammation.